2023
DOI: 10.3389/fmicb.2023.1188458
|View full text |Cite
|
Sign up to set email alerts
|

Association between gut microbiota and endometriosis: a two-sample Mendelian randomization study

Xuan Ji,
Qi Yang,
Xiu-Lin Zhu
et al.

Abstract: BackgroundRecent studies have shown that an imbalance in gut microbiota (GM) may not always be associated with endometriosis (EMS). To investigate this further, we conducted a two-sample Mendelian randomization study.MethodsMR analysis was performed on genome-wide association study (GWAS) summary statistics of GM and EMS. Specifically, the MiBioGen microbiota GWAS (N = 18,340) was used as exposure. The FinnGen study GWAS (8,288 EMS cases and 68,969 controls) was used as outcome. We primarily used the inverse v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The first two exert protective effects against the fallopian tube, vagina, and rectovaginal septum endometriosis, as well as endometriosis-related infertility, whereas the third poses a risk for intestinal endometriosis. Past research has established a causal link between Ruminococcaceae and endometriosis ( Ji et al, 2023 ). Ruminococcaceae is known primarily for producing acetic acid ( Chassard and Bernalier-Donadille, 2006 ), and some members follow a succinate pathway with succinate as the end product instead of propionate ( Louis and Flint, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first two exert protective effects against the fallopian tube, vagina, and rectovaginal septum endometriosis, as well as endometriosis-related infertility, whereas the third poses a risk for intestinal endometriosis. Past research has established a causal link between Ruminococcaceae and endometriosis ( Ji et al, 2023 ). Ruminococcaceae is known primarily for producing acetic acid ( Chassard and Bernalier-Donadille, 2006 ), and some members follow a succinate pathway with succinate as the end product instead of propionate ( Louis and Flint, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcaceae is known primarily for producing acetic acid ( Chassard and Bernalier-Donadille, 2006 ), and some members follow a succinate pathway with succinate as the end product instead of propionate ( Louis and Flint, 2017 ). Ji et al (2023) suggested that the divergent abilities of Ruminococcaceae members to produce butyrate might account for the contrasting causal relationships within the Ruminococcaceae family. Further investigation is required to explore these aspects in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A two-sample Mendelian randomization (MR) study confirms that a total of 8 gut microbiota taxa are associated with endometriosis, among which the Class-Melainabacteria, family-Ruminococcaceae, and genus-Eubacteriumruminantium had a protective effect on endometriosis, while order-Bacillales, family-Prevotellaceae, genus-Anaerotruncus, genus-Olsenella, and genus-RuminococcaceaeUCG002 may increase the risk of endometriosis. These taxa may be used for indirect diagnosis of endometriosis (Ji et al, 2023). More and more evidence observed that gut microbiota may affect endometriosis through gut microbiota-derived metabolites, which provides a new direction for early diagnosis of Endometriosis.…”
Section: Diagnosismentioning
confidence: 99%